2011
DOI: 10.1113/jphysiol.2011.215160
|View full text |Cite
|
Sign up to set email alerts
|

The primate reticulospinal tract, hand function and functional recovery

Abstract: The primate reticulospinal tract is usually considered to control proximal and axial muscles, and to be involved mainly in gross movements such as locomotion, reaching and posture. This contrasts with the corticospinal tract, which is thought to be involved in fine control, particularly of independent finger movements. Recent data provide evidence that the reticulospinal tract can exert some influence over hand movements. Although clearly secondary to the corticospinal tract in healthy function, this could ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
257
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(266 citation statements)
references
References 83 publications
5
257
1
Order By: Relevance
“…5F). Functional implications of this increased projection (e.g., with respect to progressive poststroke flexor-tone) remain to be elucidated (Bach and Magoun, 1947;Welmer et al, 2010). The oral spinal trigeminal nucleus on the right side on average increased its projections to the left, stroke-affected hemicord whereby this response was variable across individual animals and absolute numbers of labeled cells remained low ( Fig.…”
Section: Raphe Nuclei and The Lateral Vestibular Nucleus Increase Thementioning
confidence: 99%
“…5F). Functional implications of this increased projection (e.g., with respect to progressive poststroke flexor-tone) remain to be elucidated (Bach and Magoun, 1947;Welmer et al, 2010). The oral spinal trigeminal nucleus on the right side on average increased its projections to the left, stroke-affected hemicord whereby this response was variable across individual animals and absolute numbers of labeled cells remained low ( Fig.…”
Section: Raphe Nuclei and The Lateral Vestibular Nucleus Increase Thementioning
confidence: 99%
“…Thus we distinguish two pontine reticulospinal pathways to spinal MNs, one uncrossed and the other crossed, of which the uncrossed pathway transmits more faithfully and appears to be more direct. motor control; descending pathways; brain stem; spinal cord; trunk; limb THE MAMMALIAN RETICULOSPINAL system, consisting of the mesencephalic, pontine, and medullary reticulospinal pathways, is crucial for the control of skeletal musculature (Baker 2011;Kuypers 1964;Lemon 2008;Perreault and Glover 2013;Peterson 1979;Pettersson et al 2007), but the neural mechanisms by which it initiates and regulates movement are far from understood.Electrical stimulation has been a key method in studying the organization of the mammalian reticulospinal system, revealing excitatory reticulospinal connections (mono-and polysynaptic) with axial motoneurons (MNs), proximal and distal limb MNs, and digit MNs in a variety of species (monkey: Davidson and Buford 2006;Riddle et al 2009; cat: Drew and Rossignol 1990b;Galea et al 2010;Grillner et al 1968;Jankowska et al 2003;Lloyd 1941;Peterson et al 1979;Sprague and Chambers 1954;Wilson and Yoshida 1969; rat: Bolzoni et al 2013; Floeter and Lev-Tov 1993;Umeda et al 2010; and mouse: Alstermark and Ogawa 2004;Szokol et al 2008). However, many studies have not differentiated among different areas of the reticular formation (RF) that project to the spinal cord.…”
mentioning
confidence: 99%
“…Thus we distinguish two pontine reticulospinal pathways to spinal MNs, one uncrossed and the other crossed, of which the uncrossed pathway transmits more faithfully and appears to be more direct. motor control; descending pathways; brain stem; spinal cord; trunk; limb THE MAMMALIAN RETICULOSPINAL system, consisting of the mesencephalic, pontine, and medullary reticulospinal pathways, is crucial for the control of skeletal musculature (Baker 2011;Kuypers 1964;Lemon 2008;Perreault and Glover 2013;Peterson 1979;Pettersson et al 2007), but the neural mechanisms by which it initiates and regulates movement are far from understood.…”
mentioning
confidence: 99%
“…Previous studies on spinal cord injury patients found that intermuscular coherence in ␣-band may be spinal in origin (Norton et al, 2003(Norton et al, , 2004. On the other hand, a recent study suggested that ␥-band coherence may represent inputs from subcortical pathways, such as the reticulospinal and/or rubrospinal tracts (Nishimura et al 2009), which play an important role in motor control of various functional hand movements (Baker 2011). ␥-Band corticomuscular coherence was also found to increase specifically during strong isometric grip exertions (Brown 2000).…”
Section: Proximal: Distal Neural Couplingmentioning
confidence: 99%
“…Different arm configurations involve different levels of energy expenditure, which may affect motor planning of the UE dynamics , including grip force production. Change in the proximal joint use may differently excite/ inhibit multijoint spinal/subcortical pathways used during voluntary arm movements (e.g., Bullock et al 1988) that could also affect hand muscle use (Baker 2011). Alternatively, grip force production may be affected by involuntary coupling between distal and proximal UE muscles during planning (d'Avella et al 2006;Santello et al 1998) or execution (Lee et al 2014).…”
mentioning
confidence: 99%